PERBEDAAN KEMAMPUAN MEMECAHKAN MASALAH DAN RETENSI MENGGUNAKAN MODEL PBL (PROBLEM BASED LEARNING) DAN CERAMAH BERVARIASI PADA MATERI KEANEKARAGAMAN HAYATI INDONESIA SISWA KELAS X MIA SMA NEGERI 2 SURAKARTA TAHUN PELAJARAN 2014/2015 - Tri Utami Widayati; Baskoro Adi Prayitno; Joko Ariyanto (BIO-PEDAGOGI, 2015)
This research aims to find out: (1) The difference of problem solving skill between PBL model and lectures varies in the Indonesian biodiversity material of X MIA grade of SMAN 2 Surakarta in academy year 2014/2015; (2) The difference of retention between PBL model and lectures varies in the Indonesian biodiversity material of X MIA grade of SMAN 2 Surakarta in academy year 2014/2015. This research was quasi experiment research with using postest only nonequivalent control group design. The population of the research was all student of grade X MIA of SMAN 2 Surakarta as much as five grades. The sampling technique of the research used cluster sampling, therefore the X MIA 5 grade becomes the first experimental class and the X MIA 4 grade becomes the second experimental class.  The sampling technique is taken from the test and non-test. The test is used in order to measure the problem solving skill and retention. Problem solving test used to measure the problem solving skill. Posttest and retest used to measure the retention.  Retest have done in two weeks after the posttest. Non-test is an observation sheets used to measure syntaxes occurrence, documentation is used to collect the data in order to gain the equality test. The result of the hypothesis test by the t test for the difference of problem solving skill between PBL model and lectures varies show the signification value in 0,00 (sig.<0,05) and the value of tcount is 5,654. Problem solving skill with PBL model is better than lectures varies. The signification value of the difference of retention between PBL model and the lectures varies as big as 0,00 (sig.<0,05) and the value of tcount is 5,627. Retention with PBL model is better than lectures varies. The result of the research summarizes that there is differences of problem solving skill between PBL model and the lectures varies in the Indonesian biodiversity material of X MIA grade of SMAN 2 Surakarta in academy year 2014/2015 and there is differences of retention between PBL model and lectures varies in the Indonesian biodiversity material of X MIA grade of SMAN 2 Surakarta in academy year 2014/2015.            Keywords: Problem Based Learning Model, the lectures varies, problem solving skill, retention,